2008
DOI: 10.2478/s11534-008-0025-1
|View full text |Cite
|
Sign up to set email alerts
|

Photochromism and magneto-optic response of ZnO:Mn semiconductor quantum dots fabricated by microemulsion route

Abstract: Abstract:ZnO:Mn semiconductor quantum dots were prepared by solution casting led microemulsion route. Quantum dots of average size ∼2 nm were noticed in transmission electron micrographs. The present work highlights colour change phenomena (photochromic effect) of quantum dots while subjected to photon illumination. The magneto-optic measurements e.g. magnetic field (H) vs angle of rotation (θ) show step like behavior and is ascribed to the quantum confinement effect of diluted magnetic ZnO:Mn nanostructures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…If this is caused by the absorption of light, as in the current case, this phenomenon is referred to as photochromism. It is known to occur in numerous organic and inorganic materials, of which many are Eu-activated phosphors. From this list, Ca­Al 2 O 4 :Eu 2+ ,Nd 3+ is also known as a persistent phosphor, but in contrast to the case of SrAl 2 O 4 :Eu 2+ ,Dy 3+ it seems that the absorption bands of the color center do not show overlap with the absorption bands of the Eu 2+ activator, although it is yet unclear whether the color centers in CaAl 2 O 4 :Eu 2+ ,Nd 3+ are also responsible for the trapping related to the persistent luminescence as is the case for SrAl 2 O 4 :Eu 2+ ,Dy 3+ …”
Section: Results and Discussionmentioning
confidence: 99%
“…If this is caused by the absorption of light, as in the current case, this phenomenon is referred to as photochromism. It is known to occur in numerous organic and inorganic materials, of which many are Eu-activated phosphors. From this list, Ca­Al 2 O 4 :Eu 2+ ,Nd 3+ is also known as a persistent phosphor, but in contrast to the case of SrAl 2 O 4 :Eu 2+ ,Dy 3+ it seems that the absorption bands of the color center do not show overlap with the absorption bands of the Eu 2+ activator, although it is yet unclear whether the color centers in CaAl 2 O 4 :Eu 2+ ,Nd 3+ are also responsible for the trapping related to the persistent luminescence as is the case for SrAl 2 O 4 :Eu 2+ ,Dy 3+ …”
Section: Results and Discussionmentioning
confidence: 99%
“…All the described mechanisms have their own merits and limitations. In a recent work, an appreciable photochromism was demonstrated in Mn incorporated ZnO nanosystems (Misra et al 2008). At present, it is difficult to predict a suitable model that fits well to our system, but we expect that the overall cause is due to the transitory variation of the oxidation state of W as a result of absorption of em radiation by the tungsten oxide system.…”
Section: Photochromic Propertiesmentioning
confidence: 87%
“…Faraday active materials are used as optical isolators and magnetic field sensors, among other applications [49]. Santiago [52]. Savchuk et al [53] and Oliveira et al [54] reported FE for Mn doped ZnO with different wavelengths.…”
Section: Introductionmentioning
confidence: 99%